2013
DOI: 10.1111/jrh.12009
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Healthy Eating Among Appalachian Residents

Abstract: Purpose Extensive attention has been focused on improving the dietary intake of Americans. Such focus is warranted due to increasing rates of overweight, obesity, and other dietary-related disease. To address suboptimal dietary intake requires an improved, contextualized understanding of the multiple and intersecting influences on healthy eating, particularly among those populations at greatest risk of and from poor diet, including rural residents. Methods During 8 focus groups (N=99) and 6 group key informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…Residents of rural communities often face added economic challenges of food insecurity and unemployment (Appalachian Regional Commission, ). Research on Appalachian adults’ food choices has found that food knowledge, intra‐family norms, and community social networks influence food choices (Schoenberg, Howell, Swanson, Grosh, & Bardach, ). These multilevel influences underscore the importance of assessing food access from a socio‐ecological perspective, including the individual (consumer) and community food environment.…”
Section: Introductionmentioning
confidence: 99%
“…Residents of rural communities often face added economic challenges of food insecurity and unemployment (Appalachian Regional Commission, ). Research on Appalachian adults’ food choices has found that food knowledge, intra‐family norms, and community social networks influence food choices (Schoenberg, Howell, Swanson, Grosh, & Bardach, ). These multilevel influences underscore the importance of assessing food access from a socio‐ecological perspective, including the individual (consumer) and community food environment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low number of class participants, the nominal group sessions conducted prior to intervention development revealed barriers and enhancements to healthy eating that paralleled motivation to participate in cooking classes (13). Subsequent focus group research in Appalachia has reported similar findings (27). Additional qualitative, quantitative and mixed methods studies reflect the importance of pre-intervention assessment of the barriers to and facilitators of healthy eating in several populations worldwide (2839).…”
Section: Resultsmentioning
confidence: 58%
“…Questionnaire responses indicated general impressions of specific aspects of each theme validated in the Rural Nutrition Care Model. 15 Some sample questionnaire topics can be found in Gutschall et al 16 or by writing the lead author of this article.…”
Section: Methodsmentioning
confidence: 99%
“…15 Residents there identify the need for modified health behaviors and improved quality health care in Appalachia. 11,16 A complete understanding of the local culture could help serve this population's health care and nutrition needs, 17 whereas violation of these cultural norms may create additional barriers to meeting those needs. Adequate and accurate nutrition information is critically important in a region plagued by chronic disease.…”
mentioning
confidence: 99%